The Influence of Organizational Justice and Quality of Work Life on Job Involvement among Service Department Employees at PT. Gemilang Berlian Indah, Pontianak Branch - Andi Purwanto Purba; Eru Ahmadia (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the influence of Organizational Justice and Quality of Work Life on Job Involvement among employees of the Service Department at PT. Gemilang Berlian Indah, Pontianak Branch. The research method employed is quantitative associative with a total sampling technique involving 53 respondents. Data were analyzed using multiple linear regression through SPSS version 25. The results indicate that the regression model is significant, with a value of F-count = 20.917 F-table = 3.18 and Sig. = 0.000 0.05, which means that both independent variables simultaneously have a positive and significant effect on job involvement. Partially, Organizational Justice has a positive and significant effect on Job Involvement, and Quality of Work Life also shows a positive and significant influence on Job Involvement. The correlation coefficient (R) of 0.675 indicates a strong relationship between the variables, while the coefficient of determination (R²) of 0.456 shows that 45.6% of the variation in job involvement is influenced by organizational justice and quality of work life, with the remaining 54.4% affected by other factors beyond this study. The study concludes that implementing fairness and improving work quality can strengthen employee involvement. Future research is recommended to include other variables such as work motivation, leadership style, or organizational culture to provide a more comprehensive understanding of the factors influencing employee job involvement.